THE IMPLEMENTATION OF PUBLIC SECTOR PERFORMANCE MEASUREMENT WITH BALANCED SCORECARD WITH STAKEHOLDER PERSPECTIVE (CASE STUDY ON RSUD DR. SOETOMO SURABAYA) - Andik Lukman Hakim; Achmad Zaky (Jurnal Ilmiah Mahasiswa FEB, 2014)
Performance measurement  is a  benchmark of  progress  in  achieving  the goals and objectives that have been set previously. This research aims to measure the  organization’s  performance  using  the  Balanced  Scorecard with  stakeholder perspective. The  object  of  this  research  is  Rumah  Sakit  Umum  Daerah  Dr. Soetomo Surabaya. This  research  is a descriptive qualitative  research with case study approach. Balanced Scorecard perspective used in this research is financial perspective,  stakeholder  perspective,  internal  business  process  perspective,  and growth and learn perspective. Measurement is done by comparing the realization with  the  target or  ideal  criteria  that  have  been  set. The  comparison  results  are given a score for each indicator is then used to score each perspective. Based on the results, the ratio of the value of each perspective everything is above 1, which means  that  the  overall  realization  of  the  performance  exceeds  the  set  targets. While  the  final  score  indicates  that  the  stakeholder  perspective  has  the highest value compared to other perspectives. This is consistent with the objectives of the organization  that  promotes  the  maximization  of  service  to  stakeholders.  With these  results  it  can  be  concluded  that  the  performance  of  the  organization  in general can be said to be good.Keywords: performance  measurement,  balanced  scorecard,  and  stakeholder perspective